REPRESENTASI SOSIAL SANTRI DAN KOTA DALAM NOVEL HUBBU KARYA MASHURI (SEBUAH TINJAUAN SOSIOLOGI SASTRA) - Muhtarom, Imam (SUAR BETANG, 2019)
Mashuri?s Hubbu is all about the life of a santri which was not always inline with the schools? rules. This novel takes a picture of a failed santri. The main actor of the novel, Jarot, have had not succeed of holding the schools principles. He broke the rules when attending lectures in Surabaya. This is a sociology of literature point of view paper. It figures out the city?s social realities which change the life of the actor. It also identifies how the novel get its social basic. In this sense, Hubbu is a social representation of reality. The novel provides values dispute when a santri live in outer world which is actually his real life. He should adapt to this different environment without losing his previous status? He can also be rolled up by seculary values offered by the life of the city.